A family of FeIII4LnIII4 clusters containing derivatised salicylaldoximate ligand: Syntheses, structures and magnetic properties. (16th August 2017) - Chen, Hui; Ma, Cheng-Bing; Sun, Lei; Chen, Chang-Neng
Graphical abstract: A family of Fe III 4 Ln III 4 clusters containing 3-methyloxysalicylaldoximate ligand has been prepared, and their crystal structures and magnetic properties have been studied. Among them, compound Fe III 4 Dy III 4 exhibits frequency-dependent out-of-phase ac susceptibility signals indicative of slow magnetization relaxation. Abstract: A family of octanuclear clusters [Fe III 4 Ln III 4 O2 (OH)4 (mosaoH)4 (Piv)4 (N-mdea)4 (H2 O)2 ] [Ln = Y(1 ), Gd(2 ), Tb(3 ) and Dy(4 ), mosaoH2 = 3-Methyloxysalicylaldoxime, N-mdeaH2 = N-methyl diethanolamine, pivH = pivalic acid] has been prepared by reactions of [Fe3 O(piv)6 (OH2 )2 (OH)]·H2 O with Ln(NO3 )3 ·6H2 O, mosaoH2 and N-mdeaH2 ligands. The crystal structures of1 –4 were obtained, and their core can be described as two distorted tetrahedral subunits of [Fe2 Ln2 (μ4 –O)] connected by a pair of μ3 –OH − groups. A dc magnetic susceptibility study reveals that there exist strong antiferromagnetic interactions between the neibouring Fe atoms. Fitting of the susceptibility data of compound1 containing diamagnetic Y III ions gives J = −127 cm −1 . Compound4 exhibits frequency-dependent out-of-phase ac susceptibility signals indicative of slow magnetization relaxation.